Giant super-poissonian shot noise in spin-polarized SET structures - Gorelik, L.Y.; Kulinich, S.I.; Shekhter, R.I.; Jonson, M.; Vinokur, V.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
We study transport of spin-polarized electrons through a magnetic single-electron transistor (SET) in thepresence of an external magnetic field. Assuming the SET to have a nanometer-sized central island with a single electron level, we find that the zero-frequency shot noise diverges as the on-dot spin-flip rate goes to zero, provided the source and drain leads are completely polarized in the same direction. We present an analyticalexpression for the low-frequency super-poissonian shot noise that allows one to specify the necessary conditions for the experimental observation of the phenomenon.